Por una renovación en los estudios sobre los conflictos armados: el caso africano - Lair, Eric (Pontificia Universidad Javeriana, 2014)
For years the Cold War proposed that armed regional conflicts were evaluated in terms of the East-West confrontation to the detriment of a more local analysis. The end of this era offers opportunity to study the conflicts considering local factors.Until now, on only a few occasions the literature about armed conflicts in Africa has filled the expectations left behind by the disappearance of the antagonizing paradigm of the Cold War. A review of the recent studies done on this topic reveals that the popular focus of the East-West period has been replaced by others that tend to simplify the complexity of the war. Considering the phenomenon of the war in Africa, the question arises whether or not an "intellectual defeat" has taken place or if investigations are developing that demonstrate a better understanding of the conflicts.